Availability of green areas in the context of the 3-30-300 rule: The case study of Wolsztyn city - Szczepańska, Magdalena; Wyrwa, Klaudia (Quaestiones Geographicae, 2025)
Current recommendations for shaping greenery in the city refer to the 3-30-300 rule, i.e. providing residents of a residential building with a view of trees, direct proximity to greenery at the place of residence and pedestrian access to a high-quality public park or other area. Many cities implement this rule as part of local greening programmes. The authors analyse the structure of green areas in the city of Wolsztyn, assessing it in the context of the 3-30-300 rule. As a result, they identify areas requiring better access to greenery and propose specific actions to increase the availability of greenery within the city. The recommendations formulated can improve residents’ quality of life and the urban environment.